Science Learning Competence of Junior High School Students (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
Science is an important learning area that a student must be competent with as it deals with broad understanding of how the world works. However, Philippines ranked one of the lowest performing countries when it comes to science which indicates the need to intervene. The Junior High School Students particularly in the lower grade levels are observed to have difficulties in this particular area. The researchers aimed to describe the status of their science learning competence to identify what areas of learning science need attention. This quantitative descriptive-correlational gathered data from 56 Grade 7 and Grade 8 students using adapted survey questionnaire. Weighted mean was used to describe their science learning competence as to scientific inquiry and communication. The findings reveal that most of the respondents have high competence in their scientific inquiry but is moderately competent along their scientific communication competence. Specifically, the researchers identified that they need enhancement on the following competence as to scientific inquiry: operate experimental apparatus to measure data, draw conclusions based on the mathematical relationship among data. Moreover, they need to improve their competence as to scientific communication: use graphs or mathematical signs to describe the data content, describe data relationships through graphs or mathematical signs, convert raw data to understandable form, and ask questions about ambiguous statements from peers. The researchers recommend that the science learning competence of the students, both in scientific inquiry and communication must be continuously improved in order for them to become better in performing academically in their Science subject.
Keywords: scientific inquiry; communication; science learning competency